Democracy's discontent and civic learning : multiple perspectives - White, Charles S., 1952- (International social studies forum, the series., 2018)
Around the globe, democracy is under assault. For a dozen years, global freedom has followed a downward slope, according to Freedom House. Once viewed as the world's model of freedom, the United States has slipped in world ratings of democracy. For a rising portion of the world's population, faith in democracy is flagging. At the same time, a wave of nationalism and xenophobia is rising in the West, questioning democracy's ability to meet the needs of its citizens.The contributors to this volume examine democracy's discontent from a variety of perspectives. What forces have produced the extreme partisanship and polarization roiling America's civic life and politics? How has today's populist movement challenged democratic norms and institutions? What role has social media played in democracy's discontent and its defense? How do we overcome persistent racism in the face of emboldened White supremacist and anti-immigrant agitation?Across the pages of this book, teachers, teacher educators, and education policy makers will recognize a common theme in responding to democracy's discontent - the need to rebuild the nation's civic infrastructure. Research on best practices in civic learning and engagement serve as a guide to transforming how we prepare citizens for democratic deliberation and civic action. Creative and effective teaching materials and approaches await only the will to invest the needed time and support. Repairing our civic infrastructure will help to restore confidence in our civic capabilities and trust in our ability to work together for the public good. Without a serious recommitment to the civic mission of schools, the nation will be ill prepared to defend against those within and beyond our borders who are intent on undermining democracy.